Women's perceptions of the adoption of personalised risk-based breast cancer screening and primary prevention: a systematic review. (3rd October 2018) - Rainey, Linda; van der Waal, Daniëlle; Wengström, Yvonne; Jervaeus, Anna; Broeders, Mireille J.M.
Abstract: Introduction: Increased knowledge of breast cancer risk factors may enable a paradigm shift from the current age-based mammographic screening programmes to a personalised risk-based approach. This would warrant a significant change in practice, yet the acceptability from a woman's perspective has never been systematically explored. In this systematic review, we inventoried and appraised studies of women's perceptions of risk-based breast cancer screening and prevention to identify factors associated with adopting this new paradigm. Methods: We searched Medline, Embase and PsycInfo to identify original articles in English containing perceptions of risk-based breast cancer screening and/or primary prevention of women with an average to above average risk of developing breast cancer. Qualitative data were systematically extracted and referenced against four theoretical models of preventative health behaviour adoption. Results: When considering the adoption of this novel screening and prevention programme, women carefully review their perceived susceptibility to breast cancer. Their decisions are based on a cost–benefit analysis of adopting lifestyle changes, chemoprevention, or prophylactic surgery, taking into account their perceived competence, individual autonomy, relatedness to others, and personal preference. The role of intent is limited when considering behavioural change. Conclusions: Implementing risk-based breast cancer screening and prevention will require a multifactorial approach. The transition from theory to practice can be supported by developing evidence-based shared decision aids and family-oriented (genetic) counselling programmes.